Without a diagram, I am assuming "B" is the angle that the ladder makes with the ground, and "x" is the distance from the base of the ladder to the building.
cos B = x/30 = .2
so x = 30*.2 = 6
The height of the building is extraneous information, because we know that a 30...
Remember the Pythagorean identity, sin^2(x) + cos^2(x) = 1. If you use this to replace sin^2 with an expression containing cos^2, you can factor the expression.
So you had sin^2 (x) + 2 cos (x) - 2 = 0 and you know by the pythagorean identity that
sin^2 (x) = 1 - cos^2 (x),...
F(x, y, z) is called function notation, it is really just a substitution problem. It tells you what to substitute for x, y, and z. In your problem, f (x, -x^2, x^2) means x does not change, y is replaced with -x^2, and z is replaced with x^2.
So substitute: ( (x^2)^2 + x^2 - (-x^2)...